Selective expression of histamine receptors H1R, H2R, and H4R, but not H3R, in the human intestinal tract. Issue 4 (18th November 2005) - Sander, L E; Lorentz, A; Sellge, G; Coëffier, M; Neipp, M; Veres, T; Frieling, T; Meier, P N; Manns, M P; Bischoff, S C
Abstract : Background and aims: Histamine is known as a regulator of gastrointestinal functions, such as gastric acid production, intestinal motility, and mucosal ion secretion. Most of this knowledge has been obtained from animal studies. In contrast, in humans, expression and distribution of histamine receptors (HR) within the human gastrointestinal tract are unclear. Methods: We analysed HR expression in human gastrointestinal tissue specimens by quantitative reverse transcription-polymerase chain reaction and immunostaining. Results: We found that H1R, H2R, and H4R mRNA were expressed throughout the gastrointestinal tract, while H3R mRNA was absent. No significant differences in the distribution of HR were found between different anatomical sites (duodenum, ileum, colon, sigma, and rectum). Immunostaining of neurones and nerve fibres revealed that H3R was absent in the human enteric nervous system; however, H1R and H2R were found on ganglion cells of the myenteric plexus. Epithelial cells also expressed H1R, H2R and, to some extent, H4R. Intestinal fibroblasts exclusively expressed H1R while the muscular layers of human intestine stained positive for both H1R and H2R. Immune cells expressed mRNA and protein for H1R, H2R, and low levels of H4R. Analysis of endoscopic biopsies from patients with food allergy and irritable bowel syndrome revealed significantly elevated H1R and H2R mRNA levels compared with controls. Conclusions: We have demonstrated that H1R, H2R and, to some extent, H4R, are expressed in the human gastrointestinal tract, while H3R is absent, and we found that HR expression was altered in patients with gastrointestinal diseases.